1982
DOI: 10.1007/bf00987799
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemics produced by the hydrophyteMyriophyllum spicatum affecting mosquitoes and midges

Abstract: An extract of the hydrophyteMyriophyllum spicatum L. was found to be toxic to first- and fourth-instar larvae of the mosquitoes,Culex quinquefasciatus Say,Culex tarsalis Coquillett,Culiseta incidens (Thomson),Aedes aegypti L., and chironomid midges in the laboratory. When first-stage larvae were exposed to the extract, the lowest concentration (6.4 mg extract/100 ml H2O) produced 86,60, and 48% mortality inC. incidens, C. quinquefasciatus, andA. aegypti, respectively. Higher concentrations caused 100% mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Bioactive chemicals affecting biota have been documented for M. spicatum (Körner and Nicklisch 2002) and C. baltica (in plant extracts; WiumAndersen et al 1982), but not for P. pectinatus (Körner and Nicklisch 2002). Although such chemicals from M. spicatum have been documented as having only negative effects on invertebrates (dipterans, Dhillon et al 1982;mysids, Lindén and Lehtiniemi 2005), we cannot exclude that bioactive chemicals may have attracted other invertebrate species in the present study. The animals could also be attracted by the palatability and nutritional content of plants, which are determined by their physical and chemical properties.…”
Section: ) Andcontrasting
confidence: 51%
See 1 more Smart Citation
“…Bioactive chemicals affecting biota have been documented for M. spicatum (Körner and Nicklisch 2002) and C. baltica (in plant extracts; WiumAndersen et al 1982), but not for P. pectinatus (Körner and Nicklisch 2002). Although such chemicals from M. spicatum have been documented as having only negative effects on invertebrates (dipterans, Dhillon et al 1982;mysids, Lindén and Lehtiniemi 2005), we cannot exclude that bioactive chemicals may have attracted other invertebrate species in the present study. The animals could also be attracted by the palatability and nutritional content of plants, which are determined by their physical and chemical properties.…”
Section: ) Andcontrasting
confidence: 51%
“…Several other factors of natural plants could influence the invertebrate distributions. The animals could be affected by plantsecreted bioactive chemicals that could attract (Brönmark 1985), repel, or kill the invertebrates (Dhillon et al 1982;Lindén and Lehtiniemi 2005) or affect the periphyton food resources for the animals (Hilt 2006). Bioactive chemicals affecting biota have been documented for M. spicatum (Körner and Nicklisch 2002) and C. baltica (in plant extracts; WiumAndersen et al 1982), but not for P. pectinatus (Körner and Nicklisch 2002).…”
Section: ) Andmentioning
confidence: 99%
“…The ultimate reason for the production of repellent chemicals in aquatic macrophytes may be herbivore deterrence (Dhillon et al 1982;Cronin and Hay 1996a), gaining competitive advantage over other autotrophs (Gross 2003) or both. If the toxicity is primarily an inducible defense against herbivores, tissue damage may facilitate the production and excretion of the chemicals (Levin 1971;Cronin and Hay 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Several Myriophyllum species inhibit the growth of phytoplankton, especially cyanobacteria (reviewed in Gross 2003), and repel cladocerans (Pennak 1973;Lauridsen and Lodge 1996). Potentially the most harmful species in the genus is Myriophyllum spicatum, which has negative effects on phytoplankton (reviewed in Gross 2003), other macrophytes (Agami and Waisel 1985), and animals, such as mosquitoes and midges (Dhillon et al 1982;Johnson and Mulla 1983). Similarly, Chara spp.…”
mentioning
confidence: 99%
“…Additionally, greater water circulation in V. americana stands could guarantee other critical conditions for macroinvertebrates like higher dissolved oxygen levels than other macrophytes (Caraco and Cole, 2002). In addition, allelochemicals releasing from macrophytes decreased survival or changed behaviors of some invertebrate taxa (dipteran larvae, Dhillon et al, 1982;mysids, Lindén and Lehtiniemi, 2005), but the concentration and effectiveness of such substances varied with macrophyte species. Gross (2003) reported that allelopathic substances have been documented for M. spicatum but, are rare among submerged Potamogeton species.…”
Section: Analyzing the Effects Of Macrophyte Architectures On Zooplanmentioning
confidence: 99%